2013
DOI: 10.1603/me12270
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Selected Traps and Lures for Monitoring the Filarial and Arbovirus Vector, <I>Aedes polynesiensis</I> (Diptera: Culicidae), in French Polynesia

Abstract: The efficacy of the BG-Sentinel (BGS) and the BG-Mosquitito (BGM) mosquito traps for sampling populations of the important filariasis and dengue vector Aedes (Stegomyia) polynesiensis (Marks) was evaluated in French Polynesia against human bait collections (HBC) using a modified Centers for Disease Control and Prevention backpack aspirator. Traps were baited with BG-Lure (a combination of lactic acid, ammonia, and caproic acid) or carbon dioxide plus octenol (1-octen-3-ol) known as attractants to aedine mosqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…aegypti when using human bait collections. This finding shows that the males of some species are attracted to and orientate towards host cues in the field [23].…”
Section: Mate-findingmentioning
confidence: 66%
See 1 more Smart Citation
“…aegypti when using human bait collections. This finding shows that the males of some species are attracted to and orientate towards host cues in the field [23].…”
Section: Mate-findingmentioning
confidence: 66%
“…Hapairai et al [23] reported collecting a larger number of male than female Ae. aegypti when using human bait collections.…”
Section: Mate-findingmentioning
confidence: 99%
“…Consequently, traps can generate entomological indices more accurately, and estimate the risk of dengue, zika, and chikungunya transmission with greater precision (Barrera, 2016;Steffler et al, 2011). These traps are as effective as human bait collection, and are more effective than manual aspirators (Figueiredo et al, 2013;Hapairai et al, 2013;Maciel-de-Freitas et al, 2006. Other tools to detect high-risk clusters in a given area are Geographical Information Systems (GISs) and spatial analysis techniques, as demonstrated by Barbosa et al (2014) and Chiaravalloti-Neto et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…The trap would also be effective during the times of day when vectors are most active. Medical entomologists work towards the development of traps that meet as many of these requirements as possible [3-5]. …”
Section: Introductionmentioning
confidence: 99%